Positive solutions for the fractional Laplacian in the almost critical case in a bounded domain. (August 2017) - Figueiredo, Giovany M.; Siciliano, Gaetano
Abstract: We prove existence of multiple positive solutions for a fractional scalar field equation in a bounded domain, whenever p tends to the critical Sobolev exponent. By means of the "photography method", we prove that the topology of the domain furnishes a lower bound on the number of positive solutions.